Repeated Mild Traumatic Brain Injury: Potential Mechanisms of Damage - Fehily, B.; Fitzgerald, Melinda (SAGE PUBLICATIONS INC, 2017)
Mild traumatic brain injury (mTBI) represents a significant public healthcare concern, accounting for the majority of all head injuries. While symptoms are generally transient, some patients go on to experience long-term cognitive impairments and additional mild impacts can result in exacerbated and persisting negative outcomes. To date, studies using a range of experimental models have reported chronic behavioral deficits in the presence of axonal injury and inflammation following repeated mTBI; assessments of oxidative stress and myelin pathology have thus far been limited. However, some models employed induced acute focal damage more suggestive of moderate–severe brain injury and are therefore not relevant to repeated mTBI. Given that the nature of mechanical loading in TBI is implicated in downstream pathophysiological changes, the mechanisms of damage and chronic consequences of single and repeated closed-head mTBI remain to be fully elucidated. This review covers literature on potential mechanisms of damage following repeated mTBI, integrating known mechanisms of pathology underlying moderate–severe TBIs, with recent studies on adult rodent models relevant to direct impact injuries rather than blast-induced damage. Pathology associated with excitotoxicity and cerebral blood flow-metabolism uncoupling, oxidative stress, cell death, blood-brain barrier dysfunction, astrocyte reactivity, microglial activation, diffuse axonal injury, and dysmyelination is discussed, followed by a summary of functional deficits and preclinical assessments of therapeutic strategies. Comprehensive characterization of the pathology underlying delayed and persisting deficits following repeated mTBI is likely to facilitate further development of therapeutic strategies to limit long-term sequelae.